Influence of Sintering Temperatures on Pr0.7Ba0.3MnO3 Prepared Using Thermal Treatment Method - Hon, Xiao Tong; Lim, Kean Pah; Lau, Lik Nguong; Kechik, Mohd Mustafa Awang; Chen, Soo Kien; Shabdin, Muhammad Kashfi; Hapipi, Nurhidayah Mohd; Rohiat, Najihah; Shaari, Abdul Halim (Journal of Material Science and Radiation, 2025)
In this work, Pr0.7Ba0.3MnO3 (PBMO) was synthesised using a thermal treatment method with sintering temperature ranging from 800 °C to 1100 °C. X-ray diffraction (XRD) confirmed the formation of pure PBMO phase at 1100 °C, while lower sintering temperatures led to the presence of secondary phase, particularly Pr(Mn2O5). Microstructural analysis revealed significant grain growth with rising sintering temperatures, accompanied by enhanced crystallinity and reduced secondary phases. Magnetic measurements indicated ferromagnetic behaviour at room temperature for all samples. However, the electrical resistivity demonstrates an unexpected increase with sintering temperature, attributed to the influence of secondary phase at lower sintering temperatures and grain growth in the pure PBMO phase at higher sintering temperatures. Additionally, microstructural defects such as oxygen non-stoichiometry or porosity might further contribute to the suppression of the metal-insulator transition temperature. Overall, this study highlights the significant role of sintering temperatures in controlling the phase purity, microstructure and physical behaviour of PBMO samples, offering valuable insights for their potential applications in spintronics or magnetic sensing devices.